The development of social work undergraduate programs in Malaysia public universities: issues, challenges and opportunities - Amin, Samir Muhazzab; Mohamad, Mohd Suhaimi; Tunku Ahmad, Tunku Latifah (Universiti Putra Malaysia Press, 2019)
Since the beginning of twentieth country, social work has become an integral part of higher education systems throughout the world and becoming increasingly important due to globalization and internationalization. Therefore, development of social work program particularly at the undergraduate level in Malaysia's public universities should be given special attention in order to meet the standards. This paper is a review and analysis of the existing literature regarding the development of social work undergraduate program in Malaysia. The rigorous search from Scopus and Web of Science databases identified 15 related studies that examined broader development of social work education including the issues, and challenges as well as opportunities faced by the Malaysia's public universities in their quest to deliver a cohesive social work undergraduate program. Among the issues identified to be significant in the development of social work program in Malaysia include unqualified educator, non-existence of a professional body and act in social work, influence of western ideology, and governance issue. The issues and challenges addressed in this paper create opportunities to provide solutions including to implement further training on community development programs for social work educators, social work administration and practitioners, establishment of social work act to regulate and maintain the discipline as well as to strengthen social relationship with stakeholders in order to encourage them in facilitating the learning of alternative skills for social work program to meet the standards that can be recognized internationally.